Comparison of i-gel supraglottic airway and LMA-ProSeal™ in pediatric patients under controlled ventilation - Sai Saran; Sandeep Kumar Mishra; Ashok Shankar Badhe; Arumugam Vasudevan; Lenin Babu Elakkumanan; Gayatri Mishra (Wolters Kluwer Medknow Publications, 2014)
Background: i-gel™ and the ProSeal™ laryngeal mask airway (PLMA) are two supraglottic airway devices with gastric channel used for airway maintenance in anesthesia. This study was designed to evaluate the efficacy of i-gel compared with PLMA for airway maintenance in pediatric patients under general anesthesia with controlled ventilation. Materials and Methods: A total of 60 American Society of Anesthesiologists physical status 1 and 2 patients were included in the study and randomized to either i-gel or PLMA group. After induction of anesthesia using a standardized protocol for all the patients, one of supraglottic airway devices was inserted. Insertion parameters, ease of gastric tube insertion and fiber-optic scoring of the glottis were noted. Airway parameters such as end-tidal carbon dioxide (EtCO 2 ), peak airway pressures and leak airway pressures were noted. Patients were observed for any complications in the first 12 h of the post-operative period. Results: Both groups were comparable in terms of ease of insertion, number of attempts and other insertion parameters. Ease of gastric tube insertion, EtCO 2 , airway pressures (peak and leak airway pressure) and fiber-optic view of the glottis were comparable in both groups. There were no clinically significant complications in the first 12 h of the post-operative period. Conclusion: i-gel is as effective as PLMA in pediatric patients under controlled ventilation.